Short Communication: The effect of water quality on the population density of Pterygoplichthys pardalis in the Ciliwung River, Jakarta, Indonesia - Dewi Elfidasari; Fahma Wijayanti; HURUNIN FATHONAH MUTHMAINAH (Society for Indonesian Biodiversity, 2020)
Abstract. Elfidasari D, Wijayanti F, Muthmainah HF. 2020. Short Communication: The effect of water quality on the population density of Pterygoplichthys pardalis in the Ciliwung River, Jakarta, Indonesia. Biodiversitas 21: 4100-4106. The quality of waters is determined by the average value of the measured parameter range with a direct impact on aquatic biota due to pollution. The Ciliwung River is one of the polluted waters in Jakarta, which is the habitat for Pterygoplichthys pardalis (plecos catfish) that dominates the river. This study, therefore, aimed to analyze the influence of Ciliwung River quality on the density of P. pardalis. Data were obtained by measuring  DO, BOD, pH, rainfall, temperature, water clarity, turbidity, current velocity, river depth, ammonia, and phosphate levels, as well as the fish population density. The research result showed that the density of P. pardalis population was greatly influenced by the DO, BOD, pH, turbidity, and ammonia parameters of the Ciliwung River. The waters quality with the DO condition of 2.6 mg/L, BOD of 1,2 mg/L, pH of 7.2, the turbidity of 3.85 FTU and ammonia of 2.65 ppm were the optimum conditions for the highest population density of P. pardalis in the Ciliwung River